CFD study on combustion and emissions characteristics of methane-hydrogen co-firing in an EV burner - Sanghyeon Lee; Jaebin Lee; Byeongmin Ahn; Dowon Kang; Jeongjae Hwang; Yeseul Park; Minsung Choi (Case Studies in Thermal Engineering, 2025)
Considerable efforts are being made worldwide to convert carbon-free fuels from gas turbines in the power generation sector while focusing on reducing greenhouse gases. In this study, CFD analysis was conducted to investigate the effects of methane–hydrogen co-firing on the combustion characteristics of a gas turbine combustor for power. This study aims to explore the combustion and emissions characteristics under various operating conditions, such as different co-firing and equivalence ratios. As the hydrogen co-firing ratio increased from 0% to 60%, the flame became increasingly attached to the burner, with the OH reaction zone shifting upstream by up to 80 mm, suggesting a higher risk of flashback owing to hydrogen. The emission characteristics showed an increase in NOx, reaching approximately 140 ppm at an equivalence ratio of 0.7, as observed in both the experiments and CFD. Changes in the operating conditions based on the equivalence ratio revealed the development of an inner recirculation zone within the burner, which led to changes in the flame structure. The maximum temperature in the flame region increased to approximately 2200 K. These numerical results can serve as a reference for providing operational guidelines and assessing the feasibility of hydrogen co-firing in industrial gas turbines.